Investigation of lactate, heart rate and handgrip force Responses of climbers - Caglar Bildircin, C. (Polish Journal of Sport and Tourism, 2021)
Introduction. Sport climbing, which is included in 2020 Olympic Games, is a new sport that is both recreational and performance-focused while being the subject of scientific research all around the world. The aim of this study was to analyze the changes in lactate concentration, heart rate and handgrip forces all at once in the actual sport climbing competition.